Prognostic value of the Naples Prognostic Score in adult chronic obstructive pulmonary disease: NHANES 2005–2018 - Kang, Yue; Tan, Yingjian; Tie, Yongxin; Zhang, Yujing; Cui, Chenyu; Zhao, Yuanyuan (Frontiers in Nutrition, 2024)
Previous studies have demonstrated that the Naples Prognostic Score (NPS) provides strategic direction in the prognosis of malignant illness. Nevertheless, its relationship with chronic obstructive pulmonary disease (COPD) remains underexplored.Therefore, additional research specifically focusing on the relationship between the Naples Prognostic Score and COPD is necessary to determine its widespread applicability.The objective is to delve into the connection between NPS and the susceptibility of developing COPD.15,184 participants were included in our research and statistical analyses were performed after weighting. We employed weighted logistic regression to assess whether NPS and COPD had connection, as well as its association with lung function.Subgroup analysis to detect interaction. In addition, Kaplan-Meier survival curves were generated and adjusted hazard ratios of different causes of death were calculated by Cox regression.Our investigation examined 15,184 participants' data, then revealed a significant positive link between NPS and COPD risk, while smoking has an interactive effect on it. A trend towards an decreasing prevalence of lung function indicators such as FEV1[OR (95%CI), -339.70 (-456.53, -222.87)], FVC [OR (95%CI), -296.70 (-435.34--158.06)], FEV1/FVC [OR (95%CI), -0.03 (-0.04--0.02)]，predicted FEV1 [OR (95%CI), -0.09 (-0.14--0.04)], and predicted FVC [OR (95%CI), -0.08 (-0.15--0.01)] was observed with increased NPS level. Survival curves were drawn and Cox regression analysis was conducted by dividing participants into group 0, group 1, and group 2 with NPS of 0, 1-2 and 3-4, respectively. After assigning participants to groups 0, 1, and 2, with NPS values of 0, 1-2, and 3-4, respectively, survival curves were created and Cox regression analysis was carried out. All-cause mortality [HR (95%CI), 1.68 (1.39-2.85)] and hypertension-related mortality [HR (95%CI), 67.64 (8.88-515.07)] of group 2 were significantly elevated.The findings of this study suggest NPS serves as a robust prognostic indicator of COPD.